2001
DOI: 10.1161/hh2401.101270
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evidence for an Intracellular Site of Angiotensin Action

Abstract: Abstract-To differentiate the relative effects of nuclear and cell surface angiotensin II (Ang II) receptors, we mutated the angiotensinogen cDNA by removing the signal sequence-encoding region to produce a nonsecreted form of angiotensinogen [Ang(ϪS)Exp]. Rat hepatoma cells (which produce renin and angiotensin-converting enzyme mRNAs) were stably transfected with Ang(ϪS)Exp/pSVL (or a corresponding control) expression plasmid, and mitotic indices were measured for stably transfected cell lines. Experimental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
97
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 132 publications
(106 citation statements)
references
References 45 publications
8
97
0
1
Order By: Relevance
“…If translated, this mRNA would encode an intracellular (nonsecreted) and constitutively active form of the protein, suggesting the intriguing possibility of an intracellular pathway of angiotensin production in brain. Intracellular production of Ang-II has been proposed but remains controversial (42). The GFAP-hREN and SYN-hREN models described herein utilized a mutant renin that should essentially be constitutively active because of the cleavage of prorenin to renin by furin, a ubiquitous processing protease expressed in the brain (43).…”
Section: Discussionmentioning
confidence: 99%
“…If translated, this mRNA would encode an intracellular (nonsecreted) and constitutively active form of the protein, suggesting the intriguing possibility of an intracellular pathway of angiotensin production in brain. Intracellular production of Ang-II has been proposed but remains controversial (42). The GFAP-hREN and SYN-hREN models described herein utilized a mutant renin that should essentially be constitutively active because of the cleavage of prorenin to renin by furin, a ubiquitous processing protease expressed in the brain (43).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear angiotensin receptors were subsequently reported to be At-1-like in that they were blocked by losartan, and these reports showed receptors were present in association with both the nuclear membrane and, again, with chromatin. Confirmation that binding of angiotensin to isolated nuclei resulted in increased gene transcription was later provided by the observation that nuclear angiotensin upregulates renin, angiotensinogen, and platelet-derived growth factor (PDGF) transcription (9,10,12,47,48,(50)(51)(52)(53). Moreover, electron microscopic immunohistochemical techniques were used to demonstrate angiotensin II immunoreactivity located in association with the euchromatin of cerebellar neurons, hepatocytes, and adrenal cells from normal animals (13).…”
Section: Intracrine Renin Angiotensin Systemmentioning
confidence: 99%
“…In particular, we have shown that the large isoform of PDGF was upregulated in the transformed cells, and this effect was blocked by losartan but not candesartan CV-11974. Although it frequently has been assumed that nonpeptide angiotensin II antagonists are not internalized after receptor binding, this has not actually been shown for losartan (9,10,33,52). Indeed, a recent study employing confocal microscopy demonstrated clear internalization of angiotensin II receptors following the administration of losartan (33).…”
Section: Intracellular Angiotensinmentioning
confidence: 99%
“…Although many studies have focused on the impact of extracellular Ang II and its receptors, type 1 (AT 1 R) and type 2 (AT 2 R), on the cardiovascular system, others have reported that Ang II is also present in the intracellular compartment and can be released upon cell stretch to mediate cellular growth and/or apoptosis (1)(2)(3). Although many of the autocrine effects of this endogenous Ang store are believed to be mediated by plasma membrane Ang receptors, an intracellular RAS acting on nuclear Ang receptors has also been proposed (4,5).…”
mentioning
confidence: 99%